(untitled) (Cambridge, 2004)
A number of eminent mathematicians were invited to Bielefeld, Germany in 1999 to present lectures at a conference on topological, combinatorial and arithmetic aspects of (infinite) groups. The present volume consists of survey and research articles invited from participants in this conference. The contributions are geared to specialists and aspiring graduate and post-graduate students interested in pursuing additional research.
Keywords: Group theory; Cấu trúc đại số